ChemInform Abstract: DNA‐Protein Crosslinks: Formation, Structural Identities, and Biological Outcomes. Issue 33 (August 2015) - Tretyakova, Natalia Y.; Groehler, Arnold IV; Ji, Shaofei
Abstract Review: 68 refs.